Predlog regionalne zasnove prostorskega razvoja turizma na primeru Bele krajine - Beličič, Klemen (Geografski obzornik, 2023)
The article presents the key findings of the Master thesis, in which proposal of the regional concept of tourism development on the example of White Carniola was developed. The initial part presents the importance of tourism spatial planning. In the following, the needed analyzes for preparation of the spatial development plan of tourism was discussed. The final result of the Master's thesis presents the chosen concept of tourism development, strategic goals, measures and a map of the regional spatial development strategy for tourism.
Keywords: Bela krajina; geography of tourism; planning of tourism; prostorsko načrtovanje; razvoj turizma; regional planning; regionalni razvoj; Slovenia; Slovenija; spatial planning; turistična geografija